ANALISIS IMPLEMENTASI PRO-POOR BUDGETING PEMERINTAH KOTA SALATIGA DI MASA PENDEMI COVID-19 TAHUN 2020 - HADIWIJOYO, SURYO SAKTI; HERGIANASARI, PUTRI (Jurnal Ilmiah Widya Sosiopolitika; Vol 3 No 1 (2021): MEDIA, POLITIK, DAN PANDEMIDO - 10.24843/JIWSP.2021.v03.i01.p06, 2021)
BSTRACT The Covid-19 pandemic has implications for the welfare level of the people of Salatiga City. This study aims to analyze the implementation of Pro-Poor Budgeting in the Salatiga City Government during the Covid-19 Pandemic. The research is limited to the application of Pro-Poor Budgeting for the City of Salatiga in 2020. The method used is descriptive qualitative with interviews and field studies to the Bappeda of Salatiga City. The results of the research on the implementation of budgeting for poverty reduction programs have taken into account the principles in Pro Poor Budgeting, namely the target is the poor, focuses on the root causes of poverty, maximizes benefits for the poor and involves the participation of the poor. In conclusion, in the implementation of Pro Poor Budgeting, there are three strategic issues that are the focus of attention, namely synchronization of data on poor families with data from communities affected by Covid-19 from fostered partners owned by Regional Apparatuses, Standard Operating Procedures (SOP) for program implementation, especially those related to communities affected by Covid-19 and innovative activity programs that have the power to improve the community's economy. In addition, the success of the implementation of Pro Poor Budgeting and the handling of strategic issues is influenced by four aspects, namely bureaucratic structure, resources, disposition, and communication. Keywords : Policy Implementaion, Covid-19 Pandemic, Salatiga City Government, Pro Poor Budgeting,